BERITA AKSI REUNI 212 2019 DALAM FRAMING TEMPO.CO (EDISI NOVEMBER 2019 – FEBRUARI 2020) - Hayatunnisa Aulia; Gunawan Ikhtiono; Nirwan Syafrin (KOLONI, 2022)
Mass Media is a tool used to convey information and the reality that is happening in the community. The 212 Reunion Action is an event held to commemorate the alleged case of blasphemy against Basuki Tjahja Purnama or Ahok. the masses when selecting issues and highlighting news aspects, the author uses the Framing analysis method, which is a media analysis method. This study aims to examine the Framing of reality, the framing is a construction process, which means reality is interpreted and constructed in a certain way and meaning. The research method used is the Framing analysis method. which can reveal the differences in the media in revealing facts. The purpose of the study was to be able to see how Tempo.co's Frame or Framing was on the 212 reunion action in November 2019-February 2020. Therefore, the researcher used Framing analysis in this study, because Framing analysis is one part of text analysis. This research media uses a model. analysis of William A. Gamson and andre mondigliani. The results of this study found that the definition of Tempo.co Magazine's problem, namely Tempo.co, was considered not objective in reporting information and was considered contrary to their pro-government ideology. Keywords: Mass Media, Framing, Tempo